Development of a manual of specifications for canned mango juice (Mangifera indica Linn.) - Portus, Mariquita N.; De Leon, Sonia Y. (1978.)
This study is divided into three phases to be able to develop an manual of specifications for canned mango juice. A product profile that would come out with the critical quality attribute, based on the analysis used, was flavor. Two production batches of canned mango puree were then conducted and objective tests were performed on the raw material, in-process juice and the finished product. Control charts for variables, X and R chart of the net and gross weights were also constructed. Sensory evaluation of the product were likewise conducted, and the results of the evaluation were used as a basis for developing a manual of specifications for the canned mango juice.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Canned mango juice -- Handbooks, manuals, etc